Observation of electron runaway in a tip-plane air gap under negative nanosecond pulse voltage by PIC/MCC simulation. (1st April 2022) - Li, Yutai; Fu, Yangyang; Liu, Zhigang; Li, Handong; Wang, Peng; Luo, Haiyun; Zou, Xiaobing; Wang, Xinxin
Abstract: The initial stage of the gas breakdown with the generation of runaway electrons was investigated using particle-in-cell/Monte Carlo collision simulations. The parameters of the solved problem are a 1 mm long atmospheric air gap between tip-plane electrodes applied with a nanosecond pulse voltage. The pulse is 5.2 ns in rising time (10%–90%), 10 ns in pulse width (FWHM) and 40 kV in amplitude. The cathode is a cone-shaped electrode, the tip of which is defined by the elliptic equation (the major axis is 4 mm and the minor axis is 1 mm), and the minimum radius of curvature is 0.125 mm. As it is found in the simulation that the development of the discharge channel from the cathode to the anode only takes about tens to hundreds of picoseconds, especially at high overvoltages with runaway electrons, it is assumed that the gap voltage applied in such a short time is nearly constant. Depending on the voltage at the breakdown, different behavior of the energetic electrons is observed. When the voltage is low, about 12 kV, energetic electrons are only produced in the tip cathode layer, where the electric field is the highest; no runaway electrons leading the discharge channel are observed. When the voltage is higher, about 15 kV, the energetic electrons begin to run away at the head of the discharge channel, where the electric field is high enough. When the voltage is even higher, the energetic electrons run away, even at the beginning of the discharge, and from the cathode to the anode. Pre-ionization of the gas ahead of the discharge channel by the runaway electrons is observed, which may play an important role in the fast breakdown of the gas under the nanosecond short pulse.